Transcriptome-Guided Insights Into Plastic Degradation by the Marine Bacterium - Kumari, Alka; Bano, Nasreen; Bag, Sumit Kumar; Chaudhary, Doongar R.; Jha, Bhavanath (Frontiers in Microbiology, 2021)
Polyethylene terephthalate (PET) is a common single-use plastic which accumulated in the environment due to its non-degradable characteristics. In recent years, microbes from different environments were found to degrade plastics and suggested their capability to degrade plastics under varying environmental conditions. However, complete degradation of plastics is still a void for large-scale implications using microbes due to the lack of knowledge about genes and pathways intricate in the biodegradation process. In the present study, the growth and adherence of marine Bacillus sp. AIIW2 on PET surface instigating structural deterioration was confirmed through weight loss and hydrophobicity reduction as well as analyzing the change in bond indexes. The genome-wide comparative transcriptomic analysis of strain AIIW2 was completed to reveal the genes during PET utilization. The expression level of mRNA in the strain AIIW2 was indexed based on the log-fold change between the presence and absence of PET in the culture medium. The genes represent carbon metabolism and the cell transport system had upregulated in cells growing with PET while sporulation genes expressed highly in the absence of PET. This indicates that the strain AIIW2 hydrolyzes PET and assimilated via cellular carbon metabolism. A protein-protein interaction network was built to obtain the interaction between genes during PET utilization. The genes traced to degrade PET were confirmed by detecting the hydrolytic product of PET and genes were cloned to improve PET utilization by microbial system as an eco-friendly solution.